Feasibility Analysis Of Organic Pakcoy Farming Brassica Rapa L (Case Study on the Scientific Garden of FAPETRIK UMPAR) - Rusydi, Rusydi; Nurhapsa; Edi Kurniawan (Jurnal Agricultural Science, 2025)
This research is motivated by the importance of developing organic agricultural cultivation as an alternative to sustainable agriculture that is environmentally friendly and able to have a positive impact on consumer health, soil fertility, and environmental sustainability. Organic farming is now one of the solutions in reducing dependence on synthetic chemicals, as well as supporting environmentally sound farming systems. The FAPETRIK Scientific Garden of the University of Muhammadiyah Parepare is a potential location for the implementation and development of organic farming systems, because it is supported by adequate facilities and infrastructure, such as trial land, the availability of agricultural equipment, and access to organic materials. The purpose of this study is to determine the financial feasibility of organic pakcoy farming carried out in the plantation. The type of research used is quantitative research with a case study approach, which is to examine real conditions in one specific location. The data analysis technique used is financial feasibility analysis, which includes the calculation of production costs, revenue, and efficiency analysis through the Revenue Cost Ratio (R/C Ratio). The results of the study showed that the total income from four production times was IDR 4,235,000, while the total production cost reached IDR 4,730,500. The difference between cost and income showed a loss of IDR 495,500. The R/C Ratio value of 0.89 indicates that every IDR 1 production cost only generates IDR 0.89 in income. This shows that organic pakcoy farming in the location is not financially feasible and requires improvements in cost management and increased production in order to become an efficient and profitable business.